Kalibrasi Model Hidorologi Perubahan Tata Guna Pada Sub DAS Kampar Kanan Dalam Program HEC-HMS - Ferry Virgiawan; Bambang Sujatmoko; Mudjiatko Mudjiatko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Kampar Kanan watershed has experienced landuse changes in the recent years. It is important to be able to study about the magnitude of runoff changes due to landuse changes in Kampar Kanan watershed. Hidrologic model was extracted from HEC-GeoHMS in GIS environment to model Kampar Kanan Watershed and the effect of landuse changes on the watershed.Analysis and calibration using HEC-HMS was conducted on hydrologic model. Calibration was conducted based on observed streamflow of AWLR Danau Bingkuang and gave the value of optimized parameters which are, 120% of the initial estimated value for curve number and 150% of the initial estimated value for initial abstraction. Runoff simulation using optimized parameters and inputs of frequency storm with exceedence probability of 2% yields the streamflow magnitude of 641 cms and 617 cms for landuse simulation of 2008 and 2014 respectively. The results of HEC-HMS calculation showed a 3.7% decrease in runoff streamflow on Kampar Kanan watershed.Keywords : Calibration, hydrologic model, landuse changes, watershed, HEC-HMS,